Pengaruh Keahlian Audit dan Independensi Auditor terhadap Kinerja Auditor dengan Skeptisisme Profesional Auditor sebagai Variabel Mediasi - Jansuanti, Cicha (Jurnal KIAFE, 2025)
This study aims to examine the effects of audit expertise and auditor independence on auditor performance, with auditor professional skepticism as a mediating variable. This research employs a quantitative approach using primary data collected through questionnaires distributed to auditors working in Government Internal Supervisory Apparatus institutions, namely the Inspectorate of West Kalimantan Province, the Inspectorate of Pontianak City, and the Inspectorate of Kubu Raya Regency. The final sample consisted of 45 auditors who met the research criteria. Data were analyzed using path analysis with WarpPLS version 8.0. The results show that audit expertise has a positive and significant effect on auditor performance, while auditor independence does not have a significant direct effect on auditor performance. Auditor professional skepticism has a positive and significant effect on auditor performance. Furthermore, auditor professional skepticism does not mediate the effect of audit expertise on auditor performance. However, auditor professional skepticism mediates the positive and significant effect of auditor independence on auditor performance. These findings indicate that audit expertise directly improves auditor performance, while auditor independence contributes to auditor performance indirectly through the development of professional skepticism.